Seckel syndrome: A rare case report - Rinky Sisodia; Ravi Kadur Sundar Raj; Vipin Goel (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2014)
Seckel syndrome (SS) is a rare, autosomal recessive syndrome; characterized by severe intrauterine and postnatal growth retardation, microcephaly, mental retardation, and typical facial appearance with beaklike protrusion of the midface (bird headed). In addition to the characteristic craniofacial dysmorphism and skeletal defects, abnormalities have been described in the cardiovascular, hematopoietic, endocrine, gastrointestinal, and central nervous systems. Usually such patients have poor psychomotor development. This case report presents an 8-year-old child with SS born to parents, exposed in Bhopal gas disaster.